The Quality and Use Value of the False Flax (Camelina sativa [L.] Crantz) - Kukrić Teodora; Mladenov Velimir; Marjanović-Jeromela Ana; Stojanović Danijela (Contemporary Agriculture, 2022)
Alternative plant cultures with favorable agronomic characteristics are a great source of refined edible oil and renewable industrial oil products. False flax stands out as a species with modest growing requirements, short vegetation and diverse use. Accordingly, the breeding program of the Institute of Field and Vegetable Crops in Novi Sad created two cultivars of false flax, NS Zlatka and NS Slatka, which were the research material of this study. The use and production value of these false flax cultivars were determined by examining important seed quality characteristics: oil content, oil yield, protein content and protein yield. The highest oil content was obtained in NS Slatka (45.90%) in 2016, while the highest protein content was 30.30%. The highest oil yield (801 kg/ha in 2017) and the highest protein yield (424 kg/ha in 2017) were detected in NS Zlatka. The data obtained from the field and laboratory were analyzed by analysis of variance, Duncan test and Spearman's correlation coefficient. Statistically significant differences were identified between the cultivars, and strong environmental influence was affirmed. By examining the correlations of the analyzed features, statistically significant correlations were found. The most common fatty acids included linolenic acid (33.80%), linoleic acid (18.81%), oleic acid (15.99%), eicosenoic acid (14.22%) and erucic acid (2.90%). The results obtained are applicable in further breeding program of false flax. They are of special importance in increasing the use value of false flax owing to the oil and meal high quality and potential for even more diverse use.